2002
DOI: 10.1002/elan.200290000
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Sensors Based on Carbon Nanotubes

Abstract: Carbon nanotubes are attractive new materials. It has been about a decade since carbon nanotubes were discovered. Carbon nanotubes have many outstanding properties and have many practical or potential applications. In this short review we introduce recent advances in carbon nanotubes as potential material for electrochemical sensors. The advantages of carbon nanotubes as sensors are discussed along with future prospects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
310
0
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 579 publications
(315 citation statements)
references
References 36 publications
0
310
0
5
Order By: Relevance
“…Many biological reactions, and the nervous system chemical processes can be considered as a type of organic electrochemical process. 1,2 Therefore, a study on the electrochemical behavior of Ep is a great help in understanding the effects of the nervous system and artificial substitutes, and is of great significance to pharmacological research and the life sciences. Determination of concentrations of Ep is important for the study of neurotransmission, for diagnosis of neurological disorders, such as Parkinson's, and for developing medicines to treat the diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Many biological reactions, and the nervous system chemical processes can be considered as a type of organic electrochemical process. 1,2 Therefore, a study on the electrochemical behavior of Ep is a great help in understanding the effects of the nervous system and artificial substitutes, and is of great significance to pharmacological research and the life sciences. Determination of concentrations of Ep is important for the study of neurotransmission, for diagnosis of neurological disorders, such as Parkinson's, and for developing medicines to treat the diseases.…”
Section: Introductionmentioning
confidence: 99%
“…MWCNTs are long, multi-walled, thin cylinders of carbon that can be described as several two-dimensional graphite sheets rolled into a tube [27]. Recent studies have shown the ability of MWCNTs to promote electron transfer reactions of both important biomolecules [28,29] and redox centers embedded deep within proteins [30,31]. This electrocatalytic property, as well as the chemical stability and high mechanical strength of MWCNTs, has rendered them an appealing material for use in biosensors [32].…”
Section: Introductionmentioning
confidence: 99%
“…Because of their outstanding electrical properties such as high current densities, high electrical conductivity, and high sensitivity, they are certain to be spotlighted in future nanotechnology. Among their other attributes, single wall NTs (SWNTs) possess good sensitivity at room temperature, which offers great prospects in many future sensing applications [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%